1998
DOI: 10.1051/forest:19980701
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient cycling in deciduous forest ecosystems of the Sierra de Gata mountains: aboveground litter production and potential nutrient return

Abstract: -The potential nutrient return in a chestnut coppice (Castanea sativa Miller) over a period of 3 years (1991)(1992)(1993)(1994) has been established and compared with the returns found in four deciduous oak (Quercus pyrenaica Wild.) forests (1990)(1991)(1992)(1993) located in the Sierra de Gata mountains (central Spanish system). A convergence of abscission phenology patterns was observed among the different ecosystems studied, together with a delay in leaf fall at the warmest plot. This similarity is logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 10 publications
2
21
0
7
Order By: Relevance
“…This forest has a limited aboveground production (2.6 ± 0. 16 [8]. The site is considered a marginal area due to the low economic production and is basically appropriate for purposes of conservation of natural species.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…This forest has a limited aboveground production (2.6 ± 0. 16 [8]. The site is considered a marginal area due to the low economic production and is basically appropriate for purposes of conservation of natural species.…”
Section: Study Sitementioning
confidence: 99%
“…Studies regarding better knowledge of these forest ecosystems have been previously performed (e.g., [1,8,9,10]), mainly focused on biogeochemical cycles of nutrients. Gallardo et al [8] observed different values of Open Access *Correspondence: juanf.gallardo@csic.esproduction of these deciduous oak forests according to different areas; these differences seemed to be inversely related to the amount of annual rainfall, which caused differences in soil acidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Cole and Rapp [10] and Gallardo et al [20] have shown that N-, P-and Ca-return to the soil is mostly achieved through litterfall, while K-return is mainly due to canopy leaching; Mg is intermediate between these two possibilities and varies according to the ecosystem studied. Consequently, it is difficult to compare the results on NUE from different studies because the data are obtained from different calculations, depending on previous definitions of NUE and the ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…When requirements are greater than uptake, the plant must meet the rest of its needs for nutrients by retranslocating them from old organs to new ones. Following this line of thought, Carceller et al [8] calculated bioelement resorption as the difference between the leaf mineral mass at the end of August minus the potential return of nutrients to the soil through the leaf litter [20].…”
Section: Introductionmentioning
confidence: 99%